Porous ultrathin Cs0. 33WO3 nanosheet as well as preparation method and application thereof
By preparing porous ultra-thin Cs0.33WO3 nanosheets, the problem of insufficient response of traditional photocatalysts in the near-infrared light region is solved, efficient CO2 photocatalytic conversion is achieved, and the output and material activity are significantly improved.
Patent Information
- Application Number
- CN202411383385.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-30
- Publication Date
- 2025-01-24
- Estimated Expiration
- 2044-09-30
AI Technical Summary
Traditional semiconductor photocatalysts have limited spectral responses in ultraviolet and visible light areas, and cannot effectively utilize near-infrared light, and the adsorption and activation capabilities of CO2 molecules are poor, which limits the photocatalytic CO2 conversion activity.
The porous ultra -thin CS0.33wo3 nanometer sheet is used to prepare the preparation of the WO3 · 2H2O nano -nanoplastment, the liquid -phase peeling and solvent thermal preparation, optimize the structure and electronic structure of the material, and improve the optical activity.
The high -efficiency photocatalytic CO2 conversion is achieved under full -spectrum, visible light, and near -infrared light, and the output has been significantly improved. The active site of the material of the material is also improved.
Smart Images

Figure CN119349640A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of photocatalyst materials, and in particular to a porous ultra-thin Cs 0.33 WO3 nanosheets and their preparation method and application. Background Art
[0002] Due to the large-scale combustion of fossil fuels, global carbon dioxide emissions are increasing, posing a worrying threat to the environment and the sustainable growth of the world economy. Therefore, sustainable technologies for capturing carbon dioxide and converting it into renewable fuels and high-value chemicals have attracted considerable attention, aiming to mitigate the rising carbon dioxide concentration in the atmosphere. Among the many countermeasures, photocatalytic technology is an attractive way to use CO2 as a carbon source to produce value-added chemicals and fuels. However, traditional semiconductor photocatalysts usually have a wide band gap, and their spectral response is limited to the ultraviolet and visible light regions, and cannot effectively utilize near-infrared light, which accounts for about 50% of the solar spectrum. In addition, the poor adsorption and activation ability of CO2 molecules and the rapid recombination of photogenerated carriers still limit the photocatalytic CO2 conversion activity. Summary of the invention
[0003] The technical problem to be solved by the present invention is to study a porous ultra-thin Cs 0.33 WO3 nanosheets, preparation methods and applications thereof have near-infrared light absorption, high efficiency and high selectivity in CO2 conversion.
[0004] The technical solution of the present invention to solve the above technical problems is as follows:
[0005] A porous ultra-thin Cs 0.33 The preparation method of WO3 nanosheets comprises the following steps:
[0006] Step 1, preparing a layered WO3·2H2O nanosheet precursor: dispersing Na2WO4·4H2O in a dilute nitric acid solution, mixing, stirring, centrifuging, washing, and drying to obtain a layered WO3·2H2O nanosheet precursor;
[0007] Step 2, liquid phase exfoliation of the layered WO3·2H2O nanosheet precursor: dispersing the layered WO3·2H2O nanosheet precursor in deionized water; ultrasonic oscillation, centrifugation, filtration, and drying to obtain porous ultrathin WO3·2H2O nanosheets;
[0008] Step 3: Preparation of porous ultrathin Cs 0.33WO3 nanosheets: add porous ultrathin WO3·2H2O nanosheets to anhydrous ethanol and perform ultrasonic treatment; then add Cs2CO3 and stir until Cs2CO3 is completely dissolved; then add CH3COOH and stir to obtain a mixed solution; after the mixed solution is reacted in a reactor for a period of time, wash and dry to obtain porous ultrathin Cs 0.33 WO3 nanosheets.
[0009] Based on the above technical solution, the present invention can also be improved as follows.
[0010] Further, step 1 specifically includes: weighing Na2WO4·4H2O and dispersing it in a dilute nitric acid solution, stirring at room temperature to obtain a yellow solution, separating a yellow precipitate from the yellow solution with a centrifuge, and washing the yellow precipitate with deionized water several times until the pH value reaches neutral, and drying the yellow precipitate to obtain a layered WO3·2H2O nanosheet precursor.
[0011] Furthermore, step 2 specifically includes: dispersing the layered WO3·2H2O nanosheet precursor in deionized water, ultrasonically oscillating in a cold water bath environment to obtain a light yellow suspension, separating the unpeeled yellow precipitate in the light yellow suspension by a centrifuge, and then collecting the precipitate of the upper solution by centrifugation, and obtaining a porous ultra-thin WO3·2H2O nanosheet after drying.
[0012] Further, step 3 specifically includes: adding porous ultra-thin WO3·2H2O nanosheets into anhydrous ethanol, dispersing the powder completely in the solution after ultrasonic treatment, adding Cs2CO3, stirring the solution until it is completely dissolved, then adding CH3COOH, stirring, pouring the obtained mixed solution into a reactor to react for a period of time, collecting the sample, washing it with water and ethanol several times, and then drying it to obtain a porous ultra-thin Cs 0.33 WO3 nanosheets.
[0013] Furthermore, in step 1, the volume ratio of concentrated nitric acid to deionized water in the dilute nitric acid solution is 30-50%.
[0014] Furthermore, the above drying is all carried out in a vacuum environment.
[0015] Furthermore, in step 2, the centrifuge is used to separate the yellow precipitate in the light yellow suspension at a speed of 4000 to 7000 rpm for 3 to 10 minutes; the centrifuge is used to separate the precipitate in the upper solution at a speed of 9000 to 10000 rpm for 5 to 10 minutes.
[0016] Furthermore, in step 3, the ambient temperature of the cold water bath is 0 to 3° C., and the ultrasonic oscillation time is 5 to 18 hours.
[0017] Another technical solution of the present invention is as follows:
[0018] A porous ultra-thin Cs 0.33 WO3 nanosheets, using the above-mentioned porous ultra-thin Cs 0.33 Preparation method of WO3 nanosheets.
[0019] Another technical solution of the present invention is as follows:
[0020] A porous ultra-thin Cs 0.33 The application of WO3 nanosheets transforms the above-mentioned porous ultra-thin Cs 0.33 Preparation method of WO3 nanosheets for preparing porous ultrathin Cs 0.33 WO3 nanosheets are used in photocatalytic CO2 conversion to convert porous ultrathin Cs 0.33 The WO3 nanosheet sample was placed in a reaction tank, CH3OH was filled into the reactor, the reactor was evacuated to a vacuum, high-purity CO2 gas was introduced, and the pressure was at least equal to one atmosphere. A xenon lamp was used as a full-spectrum light source for photocatalytic experiments.
[0021] The beneficial effects of the present invention are as follows: the present invention uses porous ultra-thin WO3·2H2O nanosheets and Cs2CO3 as raw materials to prepare porous ultra-thin Cs 0.33 WO3 nanosheet photocatalyst; the preparation method of the present invention has the characteristics of simple production process, low cost and high yield; the porous ultrathin Cs 0.33 WO3 nanosheet photocatalysts not only provide a large number of active sites, but also optimize the electronic structure, thereby improving the intrinsic activity of the active sites; in addition, porous ultrathin Cs 0.33 WO3 nanosheets are beneficial to the separation and transfer of photogenerated carriers; the porous ultrathin Cs 0.33 WO3 nanosheets exhibit excellent photocatalytic CO2 conversion performance under full-spectrum light, visible light and near-infrared light irradiation. BRIEF DESCRIPTION OF THE DRAWINGS
[0022] Figure 1 The porous ultrathin Cs prepared by the present invention 0.33 WO3 nanosheets, layered Cs 0.33 WO3 and non-porous ultra-thin Cs 0.33 XRD pattern of WO3 nanosheets;
[0023] Figure 2 The layered Cs prepared in the present invention 0.33 SEM image of WO3 (a), non-porous ultra-thin Cs 0.33 TEM (b) and HRTEM (d) images of WO3 samples, porous ultra-thin Cs 0.33 TEM (c) and HRTEM images (e) of WO3 nanosheet samples;
[0024] Figure 3The porous ultrathin Cs prepared by the present invention 0.33 WO3 nanosheets, layered Cs 0.33 WO3 and non-porous ultra-thin Cs 0.33 PL spectrum of WO3 nanosheets (a), electrochemical impedance spectroscopy (b), and transient photocurrent response spectra under full spectrum and near-infrared light (c and d);
[0025] Figure 4 The porous ultrathin Cs prepared by the present invention 0.33 WO3 nanosheets, layered Cs 0.33 WO3 and non-porous ultra-thin Cs 0.33 CO2 adsorption isotherm of WO3 nanosheets (a), CO2-TPD graph (b);
[0026] Figure 5 The porous ultrathin Cs prepared by the present invention 0.33 WO3 nanosheets, layered Cs 0.33 WO3 and non-porous ultra-thin Cs 0.33 DMC yield of WO3 nanosheets under full spectrum (a) and (b) near-infrared light irradiation. DETAILED DESCRIPTION
[0027] The principles and features of the present invention are described below in conjunction with the accompanying drawings. The examples given are only used to explain the present invention and are not used to limit the scope of the present invention.
[0028] like Figures 1 to 5 As shown in the figure, a porous ultra-thin Cs 0.33 The preparation method of WO3 nanosheets comprises the following steps:
[0029] Step 1, preparing a layered WO3·2H2O nanosheet precursor: dispersing Na2WO4·4H2O in a dilute nitric acid solution, mixing, stirring, centrifuging, washing, and drying to obtain a layered WO3·2H2O nanosheet precursor;
[0030] Step 2, liquid phase exfoliation of the layered WO3·2H2O nanosheet precursor: dispersing the layered WO3·2H2O nanosheet precursor in deionized water; ultrasonic oscillation, centrifugation, filtration, and drying to obtain porous ultrathin WO3·2H2O nanosheets;
[0031] Step 3: Preparation of porous ultrathin Cs 0.33 WO3 nanosheets: add porous ultrathin WO3·2H2O nanosheets to anhydrous ethanol and perform ultrasonic treatment; then add Cs2CO3 and stir until Cs2CO3 is completely dissolved; then add CH3COOH and stir to obtain a mixed solution; after the mixed solution is reacted in a reactor for a period of time, wash and dry to obtain porous ultrathin Cs 0.33 WO3 nanosheets.
[0032] Embodiment 2 of the present invention is a porous ultra-thin Cs 0.33 The preparation method of WO3 nanosheets is based on Example 1, and step 1 specifically includes: weighing Na2WO4·4H2O and dispersing it in a dilute nitric acid solution, stirring at room temperature to obtain a yellow solution, separating a yellow precipitate from the yellow solution with a centrifuge, and washing the yellow precipitate with deionized water several times until the pH value reaches neutral, and drying the yellow precipitate to obtain a layered WO3·2H2O nanosheet precursor.
[0033] In the specific implementation, the amount of Na2WO4·4H2O used is 0.2 g; the volume of the dilute nitric acid solution is 150 mL.
[0034] Embodiment 3 of the present invention is a porous ultra-thin Cs 0.33 The preparation method of WO3 nanosheets is based on Example 2, and step 2 specifically includes: dispersing a layered WO3·2H2O nanosheet precursor in deionized water, ultrasonically oscillating in a cold water bath environment to obtain a light yellow suspension, separating the unpeeled yellow precipitate in the light yellow suspension by a centrifuge, and then collecting the precipitate of the upper solution by centrifugation, and obtaining a porous ultrathin WO3·2H2O nanosheet after drying.
[0035] Embodiment 4 of the present invention is a porous ultra-thin Cs 0.33 The preparation method of WO3 nanosheets is based on Example 3, and step 3 specifically includes: adding porous ultra-thin WO3·2H2O nanosheets to anhydrous ethanol, and dispersing the powder completely in the solution after ultrasonic treatment, adding Cs2CO3, stirring the solution until it is completely dissolved, and then adding CH3COOH and stirring. The obtained mixed solution is poured into a reactor to react for a period of time, and the sample is collected and washed with water and ethanol for several times, and then dried to obtain a porous ultra-thin Cs 0.33 WO3 nanosheets. In the specific implementation, the reactor is a 90ML polytetrafluoroethylene-lined stainless steel high-pressure reactor; the reaction temperature is 240°C, the reaction time is 30h; the dosage of Cs2CO3 is 0.036-0.038g, the volume of anhydrous ethanol is 30-60mL, and the volume of CH3COOH added is 5-20mL.
[0036] Embodiment 5 of the present invention is a porous ultra-thin Cs 0.33 The method for preparing WO3 nanosheets is based on Example 4, wherein the volume ratio of concentrated nitric acid to deionized water in the dilute nitric acid solution in step 1 is 30-50%.
[0037] Embodiment 6 of the present invention is a porous ultra-thin Cs 0.33The preparation method of WO3 nanosheets is based on Example 5, and the drying in step 1, step 2 and step 3 is all carried out in a vacuum environment. In the specific implementation, it is carried out in a vacuum drying oven.
[0038] Embodiment 7 of the present invention is a porous ultra-thin Cs 0.33 The preparation method of WO3 nanosheets is based on Example 6, wherein the rotation speed of the centrifuge in step 2 to separate the yellow precipitate in the light yellow suspension is 4000-7000 rpm, and during the specific implementation, the rotation speed is 5000-6000 rpm, and the time is 3-10 min; the rotation speed of the centrifuge to separate the precipitate in the upper solution is 9000-10000 rpm, and the time is 5-10 min.
[0039] Embodiment 8 of the present invention is a porous ultra-thin Cs 0.33 The preparation method of WO3 nanosheets is based on Example 7, wherein the ambient temperature of the cold water bath in step 3 is 0-3°C, and the ultrasonic oscillation time is 5-18h.
[0040] Embodiment 9 of the present invention is a porous ultra-thin Cs 0.33 WO3 nanosheets, using any one of the porous ultra-thin Cs 0.33 Preparation method of WO3 nanosheets.
[0041] Embodiment 10 of the present invention is a porous ultra-thin Cs 0.33 Application of WO3 nanosheets, using any one of the porous ultra-thin Cs 0.33 Preparation method of WO3 nanosheets for preparing porous ultrathin Cs 0.33 WO3 nanosheets are used in photocatalytic CO2 conversion to convert porous ultrathin Cs 0.33 The WO3 nanosheet sample was placed in a reaction tank, CH3OH was filled into the reactor, the reactor was evacuated to vacuum, high-purity CO2 gas was introduced, and the pressure was at least equal to one atmosphere. A xenon lamp was used as a full-spectrum light source for photocatalytic experiments; in addition, filters were loaded on the xenon lamp as visible light and near-infrared light sources for photocatalytic experiments. In specific implementation, the power of the xenon lamp was 300W.
[0042] The present invention uses porous ultra-thin WO3·2H2O nanosheets and Cs2CO3 as raw materials to prepare porous ultra-thin Cs2CO3 by solvent thermal method. 0.33 WO3 nanosheet photocatalyst; the preparation method of the present invention has the characteristics of simple production process, low cost and high yield; the porous ultrathin Cs 0.33 WO3 nanosheet photocatalysts not only provide a large number of active sites, but also optimize the electronic structure, thereby improving the intrinsic activity of the active sites; in addition, porous ultrathin Cs 0.33WO3 nanosheets are beneficial to the separation and transfer of photogenerated carriers; the porous ultrathin Cs 0.33 WO3 nanosheets exhibit excellent photocatalytic CO2 conversion performance under full-spectrum light, visible light and near-infrared light irradiation. Specific embodiment 1
[0044] Step 1, weigh 0.2 g of Na2WO4·4H2O and disperse it in 150 mL of dilute nitric acid solution (48 mL of concentrated nitric acid is added to 102 mL of deionized water), stir at room temperature for 72 h to obtain a yellow solution, then separate the yellow precipitate with a centrifuge, and wash the yellow precipitate with deionized water several times until the pH value reaches neutral, and dry the yellow precipitate in a vacuum drying oven at 70 ° C for 12 h to obtain a layered WO3·2H2O nanosheet precursor;
[0045] Step 2, 0.2 g of layered WO3·2H2O is dispersed in 200 mL of deionized water, and ultrasonically oscillated in a cold water bath environment at 3°C for 12 h to obtain a light yellow suspension; the unpeeled yellow precipitate in the light yellow suspension is separated by a centrifuge at a speed of 5000 rpm, and the upper layer solution is centrifuged at a speed of 10000 rpm for 10 min, the precipitate is collected, and vacuum dried in a vacuum drying oven for 12 h to obtain a porous ultrathin WO3·2H2O nanosheet;
[0046] Step 3: Add 0.18 g of porous ultrathin WO3·2H2O nanosheets to 50 mL of anhydrous ethanol, ultrasonicate for 15 min to completely disperse the powder in the solution, and add 0.036 g of Cs2CO 3, , stir the solution until Cs2CO3 is completely dissolved, then add 10mL CH3COOH and stir, pour the obtained mixed solution into a 90mL polytetrafluoroethylene-lined stainless steel autoclave and react at 240℃ for 30h, collect the samples, wash them with water and ethanol several times, and then dry them in a vacuum oven at 70℃ for 12h to obtain porous ultrathin Cs 0.33 WO3 nanosheets. Specific embodiment 2
[0048] Step 1, weigh 0.2 g of Na2WO4·4H2O and disperse it in 150 mL of dilute nitric acid solution (35 mL of concentrated nitric acid is added to 115 mL of deionized water), stir at room temperature for 72 h to obtain a yellow solution, then separate the yellow precipitate with a centrifuge, and wash the yellow precipitate with deionized water several times until the pH value reaches neutral, and dry the yellow precipitate in a vacuum drying oven at 80 ° C for 12 h to obtain a layered WO3·2H2O nanosheet precursor;
[0049] Step 2, 0.2 g of layered WO3·2H2O was dispersed in 200 mL of deionized water, and ultrasonically oscillated for 18 h at 0°C in a cold water bath environment to obtain a light yellow suspension, and the unpeeled yellow precipitate in the light yellow suspension was separated by a centrifuge at 5000 rpm, and the upper layer solution was centrifuged at 90000 rpm for 5 min, the precipitate was collected, and vacuum dried in a vacuum drying oven for 12 h to obtain a porous ultrathin WO3·2H2O nanosheet;
[0050] Step 3, 0.18g of porous ultrathin WO3·2H2O nanosheets was added to 30mL of anhydrous ethanol, and the powder was completely dispersed in the solution after ultrasonic treatment for 15min, 0.038g of Cs2CO3 was added, and the solution was stirred until Cs2CO3 was completely dissolved, and then 15mL of CH3COOH was added and stirred, and the obtained mixed solution was poured into a 90mL polytetrafluoroethylene-lined stainless steel autoclave and reacted at 240℃ for 30h. After collecting the samples, they were washed with water and ethanol several times, and then dried in a vacuum oven at 80℃ for 12h to obtain porous ultrathin Cs 0.33 WO3 nanosheets. Specific embodiment 3
[0052] Weigh 0.2 g of Na2WO4·4H2O and disperse it in 150 mL of dilute nitric acid solution (43 mL of concentrated nitric acid is added to 107 mL of deionized water). The remaining steps are the same as those in Example 1, and a porous ultrathin Cs 0.33 WO3 nanosheets.
[0053] Preparation of layered Cs 0.33 WO3 and non-porous ultra-thin Cs 0.33 WO3 nanosheet control group
[0054] Weigh 0.5 g of Na2WO4·4H2O and disperse it in 150 mL of hot water (70°C). After it is completely dissolved, add 150 mL of concentrated nitric acid to the original solution. After vigorous stirring for 72 h, a yellow solution is obtained. Then, the yellow precipitate is separated by a centrifuge and washed several times. Finally, the collected yellow precipitate is dried in a vacuum oven at 70°C for 12 h to obtain the precursor WO3·0.33H2O nanosheets.
[0055] 0.166 g WO3·0.33H2O was added to 50 mL anhydrous ethanol and ultrasonically treated for 15 min to completely disperse the powder in the solution. 0.0375 g Cs2CO3 was added and stirred for 20 min until it was completely dissolved. Then 10 mL glacial acetic acid was added and stirred for 2 h. The obtained yellow turbid liquid was sealed in a 90 mL polytetrafluoroethylene-lined autoclave and placed in an oven at 70 ° C for 30 h. After the samples were collected, they were washed with water and ethanol several times, respectively, and then dried in vacuum at 70 ° C for 12 h to obtain layered Cs 0.33 WO3, written as bulk.
[0056] Layered Cs 0.33 Liquid phase exfoliation of WO3 was performed to obtain non-porous ultra-thin Cs 0.33 WO3 nanosheets, referred to as porous-free nanosheets.
[0057] The porous ultra-thin Cs 0.33 WO3 nanosheets are referred to as porous nanosheets.
[0058] test:
[0059] Application tests were carried out on bulk, porous-free nanosheets, and porous nanosheets. The specific methods are as follows: first, 30 mg of the sample to be tested was placed in the reaction tank, and then 10 mL of CH3OH was filled into the reactor. The reactor was evacuated to a vacuum, and high-purity CO2 gas was introduced with a pressure at least equal to one atmosphere. A 300 W xenon lamp was used as a full-spectrum light source for photocatalytic experiments. In addition, filters were loaded on the xenon lamp as visible light and near-infrared light sources for photocatalytic experiments.
[0060] like Figure 1 As shown, all characteristic diffraction peaks of the three samples are completely consistent with the pure hexagonal tungsten bronze phase (JCPDS: 83-1334), indicating that the samples are of relatively high purity.
[0061] like Figure 2 As shown, the layered Cs 0.33 WO3 is an accordion-like morphology formed by the accumulation of many two-dimensional nanosheets. The super-many stacked layers are used to peel off the ultra-thin Cs 0.33 WO3 nanosheets provide a possibility. 0.33 High-density holes with a size of about 20 nm can be clearly observed on the surface of WO3 nanosheets. 0.33 The average length of WO3 nanosheets is 150nm and the width is 50nm. 0.33 The average length of WO3 nanosheets is 300nm and the width is 120nm.
[0062] like Figure 3 As shown, under the excitation wavelength of 290nm, the layered Cs 0.33 WO3 and non-porous ultra-thin Cs 0.33 WO3 nanosheets all show strong fluorescence peaks, indicating that they have a high recombination rate of photogenerated carriers. 0.33 The fluorescence peak intensity of WO3 nanosheets was significantly reduced, confirming that the introduction of the hole structure promoted the separation of photogenerated carriers. This result is consistent with its excellent photocatalytic CO2 conversion performance. Electrochemical impedance spectroscopy showed that the porous ultrathin Cs 0.33 The EIS arc diameter of WO3 nanosheets is the smallest, which means that its photogenerated carriers have a higher separation and transfer efficiency. In addition, the porous ultrathin Cs 0.33 The photocurrent intensity of WO3 nanosheets is higher than that of all other samples. 0.33 WO3 nanosheets also showed the highest photocurrent intensity under near-infrared light irradiation. These results verify that the introduction of hole structure and its combination with ultrathin structure can reduce charge transfer resistance and promote the enhancement of photocatalytic activity.
[0063] like Figure 4 As shown in the figure, the CO2 adsorption isotherm and CO2 programmed temperature desorption test were used to study the layered Cs 0.33 WO3, non-porous and porous ultra-thin Cs 0.33 The adsorption capacity of WO3 nanosheets for CO2. The ultra-thin structure has a larger contact area, which can effectively improve the adsorption capacity of active sites for CO2. When holes are introduced into the ultra-thin nanosheets, more active sites may be exposed on the surface of the material, which will further improve the adsorption capacity of the photocatalyst for CO2 and facilitate the reduction of CO2. 0.33 The desorption peak area of WO3 nanosheets is the most prominent, indicating that a stronger interaction occurs between the adsorption sites and CO2 molecules, further promoting the adsorption and activation of CO2.
[0064] like Figure 5 As shown in the figure, during the photocatalytic CO2 conversion process under full spectrum light continuous irradiation for 4 h, the main carbon-containing product is dimethyl carbonate (DMC). 0.33 The DMC yield of WO3 was poor, 0.0356 mmol g -1 (Because it is too low, Figure 5 Not shown in the figure), while the non-porous ultra-thin Cs 0.33 WO3 nanosheets slightly increased the yield of DMC to 1.053 mmol g -1 It is worth noting that when the pore structure is introduced into the porous ultrathin Cs 0.33When the DMC was deposited on WO3 nanosheets, the yield of DMC was greatly improved to 9.562 mmol g -1 , almost respectively, layered Cs 0.33 WO3 and non-porous Cs 0.33 WO3 ultra-thin nanosheets. Under near-infrared light, porous ultra-thin Cs 0.33 WO3 nanosheets all showed excellent DMC generation activity, with a conversion rate of 4.462mmolg -1 .
[0065] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principle of the present invention should be included in the protection scope of the present invention.
Claims
1. A porous ultra-thin Cs 0.33 The method for preparing WO3 nanosheets is characterized in that: The steps include: Step 1, preparing a layered WO3·2H2O nanosheet precursor: dispersing Na2WO4·4H2O in a dilute nitric acid solution, mixing, stirring, centrifuging, washing, and drying to obtain a layered WO3·2H2O nanosheet precursor; Step 2, liquid phase exfoliation of the layered WO3·2H2O nanosheet precursor: dispersing the layered WO3·2H2O nanosheet precursor in deionized water; ultrasonic oscillation, centrifugation, filtration, and drying to obtain porous ultrathin WO3·2H2O nanosheets; Step 3: Preparation of porous ultrathin Cs 0.33 WO3 nanosheets: add porous ultra-thin WO3·2H2O nanosheets to anhydrous ethanol and perform ultrasonic treatment; then add Cs2CO3 and stir until Cs2CO3 is completely dissolved; then add CH3COOH and stir to obtain a mixed solution; after the mixed solution is reacted in a reactor for a period of time; Wash and dry to obtain porous ultrathin Cs 0.33 WO3 nanosheets.
2. A porous ultra-thin Cs according to claim 1 0.33 The method for preparing WO3 nanosheets is characterized in that: The step 1 specifically comprises: weighing Na2WO4·4H2O and dispersing it in a dilute nitric acid solution, stirring at room temperature to obtain a yellow solution, separating a yellow precipitate from the yellow solution by a centrifuge, and washing the yellow precipitate with deionized water for several times until the pH value reaches neutral, and drying the yellow precipitate to obtain a layered WO3·2H2O nanosheet precursor.
3. A porous ultra-thin Cs according to claim 2 0.33 The method for preparing WO3 nanosheets is characterized in that: The step 2 specifically comprises: dispersing the layered WO3·2H2O nanosheet precursor in deionized water, ultrasonically oscillating in a cold water bath environment to obtain a light yellow suspension, separating the unpeeled yellow precipitate in the light yellow suspension by a centrifuge, and then collecting the precipitate of the upper solution by centrifugation, and obtaining a porous ultra-thin WO3·2H2O nanosheet after drying.
4. A porous ultra-thin Cs according to claim 3 0.33 The method for preparing WO3 nanosheets is characterized in that: The step 3 specifically comprises: adding porous ultra-thin WO3·2H2O nanosheets into anhydrous ethanol, dispersing the powder completely in the solution after ultrasonic treatment, adding Cs2CO3, stirring the solution until it is completely dissolved, then adding CH3COOH, stirring, pouring the obtained mixed solution into a reactor to react for a period of time, collecting the sample, washing it with water and ethanol for several times, and then drying it to obtain a porous ultra-thin Cs 0.33 WO3 nanosheets.
5. A porous ultra-thin Cs according to claim 4 0.33 The method for preparing WO3 nanosheets is characterized in that: In the step 1, the volume ratio of concentrated nitric acid to deionized water in the dilute nitric acid solution is 30-50%.
6. A porous ultra-thin Cs according to claim 5 0.33 The method for preparing WO3 nanosheets is characterized in that: The drying in step 1, step 2 and step 3 is all performed in a vacuum environment.
7. A porous ultra-thin Cs according to claim 6 0.33 The method for preparing WO3 nanosheets is characterized in that: In the step 2, the centrifuge is used to separate the yellow precipitate in the light yellow suspension at a rotation speed of 4000-7000 rpm for 3-10 min; the centrifuge is used to separate the precipitate in the upper solution at a rotation speed of 9000-10000 rpm for 5-10 min.
8. A porous ultra-thin Cs according to claim 7 0.33 The method for preparing WO3 nanosheets is characterized in that: In step 3, the ambient temperature of the cold water bath is 0-3° C., and the ultrasonic oscillation time is 5-18 h.
9. A porous ultra-thin Cs 0.33 WO3 nanosheets, characterized in that Using a porous ultra-thin Cs 0.33 Preparation method of WO3 nanosheets.
10. A porous ultra-thin Cs 0.33 The application of WO3 nanosheets is characterized by: A porous ultra-thin Cs 0.33 Preparation method of WO3 nanosheets for preparing porous ultrathin Cs 0.33 WO3 nanosheets are used in photocatalytic CO2 conversion to convert porous ultrathin Cs 0.33 The WO3 nanosheet sample was placed in a reaction tank, CH3OH was filled into the reactor, the reactor was evacuated to a vacuum, high-purity CO2 gas was introduced, and the pressure was at least equal to one atmosphere. A xenon lamp was used as a full-spectrum light source for photocatalytic experiments.
Citation Information
Patent Citations
Cesium tungsten bronze powder and preparation method thereof
CN102320662A
CsxWOyFz powder and preparation method thereof
CN103708558A
Nitrogen-doped composite photocatalyst and preparation method thereof
CN109622007A
Sheet-shaped cesium tungsten bronze nano powder as well as preparation method and application thereof
CN109761282A
In-situ synthesis method of CsxWO3-SiO2 composite aerogel
CN111589384A